The Implementation of Local Culture on Students' Career Advancement Decisions. - Fitri, Novita; Hapni, Elida; Irman, Irman; Sunawan, Sunawan (MARAWA: Jurnal Masyarakat Religius dan Berwawasan, 2023)
One of the factors that plays a role in students' career planning is local culture. In the Kuranji environment, there are students facing obstacles in career planning. Therefore, the aim of this research is to understand the role of local culture in the career decisions of students at SMAN 16 Kuranji Padang. The research method used is Participatory Action Research (PAR), a type of research that involves active participation of participants in the research process, from planning to implementation and evaluation. Data is obtained through direct participation with the research subjects. After obtaining the data, descriptive analysis will be conducted. The research results indicate that the local culture influencing students' career plans includes: the role of parents in supporting students' career plans, learning awareness demonstrated by students' discipline in attending classes on time, communication skills of students with parents and peers, and self-esteem and confidence to plan for a better career.